A review of the role of surgery for small cell lung cancer and the potential prognostic value of enumeration of circulating tumor cells. Issue 9 (September 2016) - Hamilton, G.; Rath, B.; Ulsperger, E.
Abstract: Small cell lung cancer (SCLC) is disseminated in the majority of patients at first presentation and, thus, treated with chemoradiotherapy. Despite initial high response rates, chemoresistance appears rapidly and results in a dismal prognosis. However, patients with limited cancer may exhibit better disease control upon surgical treatment. Correct staging is highly critical in the selection of those patients which are likely to benefit from surgery. Studies of the inclusion of surgery in the multimodal treatment of SCLC vary widely in number of patients, selection, treatment and follow-up. Nevertheless surgical therapy for confined SCLCs achieves favorable long-term survival compared to chemoradiotherapy, depending on a precise assessment of the degree of tumor dissemination. Recently, extremely high counts of circulating tumor cells (CTCs) were reported in patients with SCLC compared to other malignancies. In several studies the number of CTCs was found to constitute a prognostic parameter and a marker of response to therapy. Therefore, the assessment of CTCs as so-called "Liquid Biopsy" seems to constitute a more precise method to detect tumor dissemination earlier when compared to clinical staging. In conclusion, in the era of precision oncology enumeration and identification of CTCs of SCLC patients have the potential to help in the selection of patients most suitable for tumor surgery.